Sayings of the Ancestors The spiritual life of the Sibundoy Indians - Mcdowell, John Holmes (Lexington (Kentucky) : The University Press of Kentucky, 1989)
1. Introduction
2. Muscuycunamanda
3. Tapiacunamanda
4. The Ancestral World
4. The Spirit Realm
5. The Cycle of Code Application
6. Sibundoy Folk Religion
bibliogr.